Impact of whole-body vibration exercise on physical performance and bone turnover in patients with monoclonal gammopathy of undetermined significance - Lothar Seefried; Franca Genest; Johanna Strömsdörfer; Bernhard Engelmann; Constantin Lapa; Franz Jakob; Freerk T. Baumann; Billy Sperlich; Franziska Jundt (Journal of Bone Oncology, 2020)
Objective: Monoclonal Gammopathy of Undetermined Significance (MGUS) is a risk factor for reduced physical performance, osteoporosis, and fractures due to compromised musculoskeletal metabolism. In this condition it is unknown whether whole-body vibration (WBV) exercise favorably alters physical performance and bone metabolism. Methods: To evaluate the effect of three-months WBV exercise (30 min; 2x/week) including an optional three-month extension on physical performance, bone metabolism and bone mineral density. Endpoints included functional assessments, bone turnover markers and bone mineral density assessed by peripheral quantitative computed tomography of the tibia. Results: Fifteen MGUS patients (median age 62.0, nine female) completed the first three months of which ten completed the three-month extension. Measures of physical functioning including chair rise test, timed up and go and 6-minute walk test improved (p = 0.007; p = 0.009; p = 0.005) after three and six months of WBV exercise. Total tibial bone mineral density remained unaltered (p > 0.05). WBV exercise tended to increase levels of sclerostin (p = 0.093) with a transient increase in osteoclast resorption markers (N-terminal telopeptide of collagen type 1, tartrate resistant acid phosphatase 5b) after three months while Dickkopf-1 (p = 0.093), procollagen I N-terminal propeptide (p = 0.074) and total alkaline phosphatase (p = 0.016) appeared to decline. No exercise-related adverse events were reported. Conclusion: WBV exercise in MGUS patients improves indicators of physical performance. Observed trends in bone turnover markers and changes in distal tibial bone mineral density may indicate a regulatory effect of WBV exercise on bone metabolism and warrants further evaluation by large scale studies.